Lightweight anti-aging PVC (polyvinyl chloride) material and preparation method thereof
By combining modified hollow glass microspheres and stabilizers, the problems of aging resistance and flowability of PVC materials in children's toys have been solved, achieving high flowability, improved aging resistance and safety, making it suitable for the production of children's toys.
Patent Information
- Application Number
- CN202610057243.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-01-16
- Publication Date
- 2026-03-17
AI Technical Summary
Existing PVC materials used in children's toys suffer from poor aging resistance, insufficient low-temperature toughness, poor melt flowability, and the risk of migration of toxic and harmful substances, which affect production efficiency and safety.
A combination of modified hollow glass microspheres, calcium-zinc composite stabilizers, epoxidized soybean oil, and acrylate polymers is used to improve the compatibility between the filler and the matrix through surface modification and chemical reaction, forming a synergistic stabilizing system, improving flowability and aging resistance, and using environmentally friendly additives to reduce the risk of toxic substance migration.
It significantly improves the fluidity and aging resistance of PVC materials, reduces product defects, enhances safety and production efficiency, and meets the long-term use needs of children's toys.
Smart Images

Figure SMS_1
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of PVC materials and relates to a lightweight anti-aging PVC material and a preparation method. BACKGROUND
[0002] As a general-purpose synthetic resin, polyvinyl chloride (PVC) is widely used in the fields of building, packaging, electronic appliances and daily necessities due to its advantages of easy availability of raw materials, low cost, strong processability and excellent chemical stability. PVC materials can be adjusted by changing the proportion of additives to achieve different properties such as softness and hardness, meeting the needs of diversified products. However, there are inherent problems such as poor aging resistance and insufficient low-temperature toughness, which need to be modified and optimized by adding stabilizers, plasticizers and processing aids. In various application scenarios, PVC materials have long occupied an important raw material market for children's toys and toy parts due to their cost-effective advantage.
[0003] Children's toys have strict requirements for the safety, forming precision and appearance quality of PVC materials, and most toys and parts are formed by injection molding. However, the poor melt flowability of PVC resin due to its molecular chain structure characteristics, especially when molding thin-walled and complex structure toys, the melt filling speed in the cavity is uneven, which easily leads to insufficient filling and unbalanced pressure distribution, and then generates burrs and flashes at the corners and parting lines of the product. These defects not only affect the appearance of the toy, but also may cause safety hazards such as children eating or scratching due to the falling of burrs, and additional manpower and material resources are needed for subsequent polishing, increasing production cost and reducing production efficiency.
[0004] To improve the injection flowability of PVC materials and reduce burrs and flashes, lightweight modification has become an important research direction. By adding lightweight fillers, the melt viscosity can be reduced, the flow performance can be improved, and the weight of the toy can be reduced to better meet the needs of children holding. However, the existing lightweight modification technology has obvious shortcomings: traditional lightweight fillers have poor compatibility with PVC matrix, which easily leads to aggregation and reduces the mechanical properties of the material; some modification schemes improve the flowability at the expense of aging resistance, which cannot meet the long-term use requirements of toys; and some additives are not reasonably matched, which may cause migration of toxic and harmful substances, making it difficult to meet the safety standards for children's toys. SUMMARY
[0005] The purpose of the present application is to provide a lightweight anti-aging PVC material and a preparation method. By combining modified fillers, environmentally friendly additives and scientific processes, the pain points of traditional PVC materials such as "heavy, easy to age, toxic and unstable in processing" are successfully solved, and the application has strong technical competitiveness and market application value in the field of children's toys.
[0006] The purpose of the present application can be achieved by the following technical solutions: A light-weight and aging-resistant PVC material comprises, by weight parts: PVC resin 100 parts; modified hollow glass microbeads 5-25 parts; plasticizer 20-40 parts; composite stabilizer 2-6 parts; lubricant 0.5-2 parts; processing aid 0.5-3 parts; wherein the surface of the modified hollow glass microbeads is grafted with a silane coupling agent containing unsaturated double bonds; The composite stabilizer comprises calcium-zinc composite stabilizer and epoxy soybean oil.
[0007] The hollow glass beads are used to reduce the density of the composite material, the surface-modified organic long-chain enhances the compatibility with PVC, and the unsaturated double bonds are active sites. In the subsequent processing or use process, the double bonds and the epoxy groups of the epoxy soybean oil, or the free radicals generated by PVC under the action of heat and shear, undergo potential chemical reactions or strong physical interactions, further improving the interfacial bonding force, avoiding the decline of impact performance due to weak interface, and preventing interface debonding aging during long-term use. Acetyl tri-butyl citrate is safe, environmentally friendly, and has good compatibility with PVC, which can effectively insert between PVC molecular chains, weaken the interchain force, and provide excellent room temperature flexibility and processing plasticity. The calcium-zinc composite stabilizer absorbs hydrogen chloride generated by the thermal decomposition of PVC, blocks the autocatalytic degradation reaction, and provides the main thermal stabilization effect; the epoxy groups in the molecule of the epoxy soybean oil can rapidly react with HCl, consume the degradation products, and produce a synergistic effect with the calcium-zinc stabilizer, thereby improving the overall thermal stability of the system and enhancing the interfacial adhesion of the modified hollow glass microbeads and the matrix. Internal lubrication reduces intermolecular chain friction and promotes plasticization; external lubrication reduces the adhesion of the melt to the equipment and mold, and under the synergistic action, it ensures smooth flow of the melt, further assists in eliminating flash, and protects the hollow microbead structure. The main function of the acrylic ester polymer processing aid is to promote the melting and plasticization of PVC resin, improve the melt strength and uniformity. In this system, it is crucial to ensure the uniform dispersion of low-density modified microbeads in the viscous melt, and is a key aid for obtaining homogeneous high-performance composite materials.
[0008] As a preferred technical solution of the present application, the silane coupling agent containing unsaturated double bonds is gamma-(methacryloyloxy) propyl trimethoxysilane.
[0009] As a preferred technical solution of the present application, the density of the modified hollow glass microbeads is 0.20-0.60 g / cm 3 , and the average particle size is 10-100 μm.
[0010] As a preferred technical solution of the present application, the weight ratio of the calcium-zinc composite stabilizer to the epoxy soybean oil is 1:0.5 to 1:2.
[0011] As a preferred technical solution of the present application, the plasticizer is acetyl tributyl citrate.
[0012] As a preferred technical solution of the present application, the lubricant comprises an internal lubricant calcium stearate and an external lubricant oxidized polyethylene wax.
[0013] As a preferred technical solution of the present application, the processing aid is an acrylate polymer.
[0014] Further, a method for preparing the light-weight aging-resistant PVC material comprises the following steps: S1. Pre-mixing the modified hollow glass microbeads with 1 / 3 to 1 / 2 of the total amount of epoxy soybean oil to obtain a pre-mixed material; S2. Mixing the PVC resin, calcium-zinc composite stabilizer and internal lubricant and heating to 55-65℃; adding the plasticizer and the remaining epoxy soybean oil, continuing to mix and heat to 85-95℃; adding the pre-mixed material obtained in step S1 and the processing aid, mixing and heating to 105-115℃; finally adding the external lubricant, mixing uniformly to obtain a hot mixture; S3. Melting and extruding the hot mixture through a twin-screw extruder, granulating, and obtaining the product.
[0015] As a preferred technical solution of the present application, the pre-mixing in step S1 is carried out at 40-50℃.
[0016] Further, the light-weight aging-resistant PVC material is used in the preparation of a children's toy or a component of a children's toy.
[0017] The present application has the following advantages: (1) The modified hollow glass microbeads of the present application not only significantly reduce the material density, but also meet the gripping needs of children. The silane coupling agent grafted on the surface of the microbeads can form chemical bonding or strong physical action with the PVC matrix and the epoxy soybean oil through the unsaturated double bond, greatly improving the compatibility of the filler and the matrix, avoiding the mechanical property decline caused by the aggregation of traditional light-weight fillers, and ensuring the anti-impact ability of the toy. On the other hand, the spherical structure of the microbeads and the organic long chain on the surface play the roles of high-efficiency "ball bearing" and compatibilizer in the melt, greatly reducing the melt viscosity and improving the melt flow rate. This makes the material fill the mold more smoothly during injection molding, fundamentally effectively reducing or eliminating product defects such as "batch edge" and "burr" caused by insufficient flowability, and significantly improving the product yield and appearance quality.
[0018] (2) The calcium-zinc composite stabilizer and the epoxy soybean oil form a synergistic stable system, which can not only efficiently absorb hydrogen chloride generated by the thermal decomposition of PVC, block the self-catalytic degradation, but also strengthen the interfacial bonding by means of the epoxy groups. Meanwhile, the epoxy soybean oil has the functions of anti-oxidation and anti-ultraviolet, so that the thermal-oxidative aging life of the material is increased by 2-3 times, the material is not easy to become brittle and debonding during long-term use, and the long-term service requirement of the toy is met.
[0019] (3) The acetyl tri-butyl citrate environmentally-friendly plasticizer and the calcium-zinc composite stabilizer are selected as components without toxic and harmful substances, which can not only effectively reduce the melt viscosity, solve the problem of uneven filling during injection molding, and greatly reduce the generation of burrs and burrs, but also avoid the safety hazards of children's accidental ingestion and scratching from the source by avoiding the migration risk of phthalate and heavy metals. DETAILED DESCRIPTION
[0020] In order to further illustrate the technical means and effects adopted by the present application to achieve the predetermined object, the specific embodiments, structures, features and effects according to the present application are described in detail as follows in combination with examples.
[0021] Example 1 A light-weight anti-aging PVC material, by weight, comprises: 100 parts of PVC resin; 15 parts of modified hollow glass microspheres; 30 parts of plasticizer; 4 parts of composite stabilizer; 1.2 parts of lubricant; 1.4 parts of processing aid; The surface of the modified hollow glass microspheres is grafted with a silane coupling agent containing unsaturated double bonds. The composite stabilizer comprises 2 parts by mass of calcium-zinc composite stabilizer (purchased from Xingzhibao New Material Co., Ltd., model CZ-60) and 2 parts by mass of epoxy soybean oil.
[0022] The silane coupling agent containing unsaturated double bonds is γ-(methacryloyloxy) propyl trimethoxysilane.
[0023] The density of the modified hollow glass microspheres is 0.4 g / cm 3 , and the average particle size is 30-70 μm.
[0024] The plasticizer is acetyl tri-butyl citrate.
[0025] The lubricant comprises an internal lubricant calcium stearate and an external lubricant oxidized polyethylene wax.
[0026] The processing aid is an ethyl acrylate-methyl methacrylate copolymer.
[0027] A method for preparing the light-weight anti-aging PVC material, comprising the following steps: S1. Pre-mixing the modified hollow glass microspheres with 1 / 2 of the total amount of epoxy soybean oil to obtain a pre-mixed material; S2. Mix PVC resin, calcium-zinc composite stabilizer and internal lubricant and heat to 60°C; add plasticizer and remaining epoxidized soybean oil, continue mixing and heat to 90°C; add premix and processing aids obtained in step S1, mix and heat to 110°C; finally add external lubricant, mix well and obtain hot mix. S3. The hot mixture is melt-extruded and granulated using a twin-screw extruder to obtain the final product.
[0028] The premixing in step S1 is carried out at 45°C.
[0029] Example 2 A lightweight, aging-resistant PVC material, comprising, by weight: 100 parts PVC resin; 5 parts modified hollow glass microspheres; 20 parts plasticizer; 2 parts composite stabilizer; 0.5 parts lubricant; 0.5 parts processing aid; Among them, the surface of the modified hollow glass microspheres is grafted with a silane coupling agent containing unsaturated double bonds. The composite stabilizer comprises 0.7 parts by weight of calcium-zinc composite stabilizer (purchased from Xingzhibao New Materials Co., Ltd., model CZ-60) and 1.3 parts by weight of epoxidized soybean oil.
[0030] The silane coupling agent containing unsaturated double bonds is γ-(methacryloyloxy)propyltrimethoxysilane.
[0031] The modified hollow glass microspheres have a density of 0.4 g / cm³. 3 The average particle size is 30-70 μm.
[0032] The plasticizer is tributyl acetylcitrate.
[0033] The lubricant includes calcium stearate as an internal lubricant and oxidized polyethylene wax as an external lubricant.
[0034] The processing aid is an ethyl acrylate-methyl methacrylate copolymer.
[0035] A method for preparing the aforementioned lightweight and aging-resistant PVC material includes the following steps: S1. Modified hollow glass microspheres are premixed with 1 / 3 of the total amount of epoxidized soybean oil to obtain a premix; S2. Mix PVC resin, calcium-zinc composite stabilizer and internal lubricant and heat to 55°C; add plasticizer and remaining epoxidized soybean oil, continue mixing and heat to 85°C; add premix and processing aids obtained in step S1, mix and heat to 105°C; finally add external lubricant, mix well and obtain hot mix. S3. The hot mixture is melt-extruded and granulated using a twin-screw extruder to obtain the final product.
[0036] The premixing in step S1 is carried out at 40°C.
[0037] Example 3 A lightweight, aging-resistant PVC material, comprising, by weight: 100 parts PVC resin; 25 parts modified hollow glass microspheres; 40 parts plasticizer; 6 parts composite stabilizer; 2 parts lubricant; 3 parts processing aid; Among them, the surface of the modified hollow glass microspheres is grafted with a silane coupling agent containing unsaturated double bonds. The composite stabilizer comprises 4 parts by weight of calcium-zinc composite stabilizer (purchased from Xingzhibao New Materials Co., Ltd., model CZ-60) and 2 parts by weight of epoxidized soybean oil.
[0038] The silane coupling agent containing unsaturated double bonds is γ-(methacryloyloxy)propyltrimethoxysilane.
[0039] The modified hollow glass microspheres have a density of 0.4 g / cm³. 3 The average particle size is 30-70 μm.
[0040] The plasticizer is tributyl acetylcitrate.
[0041] The lubricant includes calcium stearate as an internal lubricant and oxidized polyethylene wax as an external lubricant.
[0042] The processing aid is an ethyl acrylate-methyl methacrylate copolymer.
[0043] A method for preparing the aforementioned lightweight and aging-resistant PVC material includes the following steps: S1. Modified hollow glass microspheres are premixed with 1 / 2 of the total amount of epoxidized soybean oil to obtain a premix; S2. Mix PVC resin, calcium-zinc composite stabilizer and internal lubricant and heat to 65°C; add plasticizer and remaining epoxidized soybean oil, continue mixing and heat to 95°C; add premix and processing aids obtained in step S1, mix and heat to 115°C; finally add external lubricant, mix well and obtain hot mix. S3. The hot mixture is melt-extruded and granulated using a twin-screw extruder to obtain the final product.
[0044] The premixing in step S1 is carried out at 50°C.
[0045] Example 4 A lightweight, aging-resistant PVC material, comprising, by weight: 100 parts PVC resin; 15 parts modified hollow glass microspheres; 30 parts plasticizer; 4 parts composite stabilizer; 1.2 parts lubricant; 1.4 parts processing aid; Among them, the surface of the modified hollow glass microspheres is grafted with a silane coupling agent containing unsaturated double bonds. The composite stabilizer comprises 2 parts by weight of calcium-zinc composite stabilizer (purchased from Xingzhibao New Materials Co., Ltd., model CZ-60) and 2 parts by weight of epoxidized soybean oil.
[0046] The silane coupling agent containing unsaturated double bonds is γ-(methacryloyloxy)propyltrimethoxysilane.
[0047] The modified hollow glass microspheres have a density of 0.4 g / cm³. 3 The average particle size is 30-70 μm.
[0048] The plasticizer is tributyl acetylcitrate.
[0049] The lubricant includes calcium stearate as an internal lubricant and oxidized polyethylene wax as an external lubricant.
[0050] The processing aid is an ethyl acrylate-methyl methacrylate copolymer.
[0051] A method for preparing the aforementioned lightweight and aging-resistant PVC material includes the following steps: S1. Modified hollow glass microspheres are premixed with 1 / 2 of the total amount of epoxidized soybean oil to obtain a premix; S2. Mix PVC resin, calcium-zinc composite stabilizer and internal lubricant and heat to 65°C; add plasticizer and remaining epoxidized soybean oil, continue mixing and heat to 95°C; add premix and processing aids obtained in step S1, mix and heat to 115°C; finally add external lubricant, mix well and obtain hot mix. S3. The hot mixture is melt-extruded and granulated using a twin-screw extruder to obtain the final product.
[0052] The premixing in step S1 is carried out at 50°C.
[0053] Comparative Example 1 Based on Example 1, the modified hollow glass microspheres were replaced with an equal mass of calcium carbonate filler, while the rest remained the same as in Example 1.
[0054] Comparative Example 2 Based on Example 1, γ-(methacryloyloxy)propyltrimethoxysilane was replaced with γ-aminopropyltriethoxysilane, while the rest remained the same as in Example 1.
[0055] Comparative Example 3 Based on Example 1, the composite stabilizer was changed to only calcium-zinc composite stabilizer, while the rest remained the same as in Example 1.
[0056] Comparative Example 4 Based on Example 1, no processing aids were added, and everything else remained the same as in Example 1.
[0057] Performance testing: Density: determined by impregnation method according to GB / T 1033.1 standard; Melt flow rate (MFR): determined according to GB / T 3682.1 standard at a temperature of 190℃ and a load of 5 kg; Notched impact strength: The impact strength of the cantilever beam was determined according to GB / T 1843 standard, with the notch type being type A (V-notch), and the test was conducted using a pendulum impact test. Aging resistance: According to the GB / T 7141-2008 standard, the thermal aging test method is carried out. The impact specimen is placed in a forced-air drying oven and continuously heated at 100℃ for 168 hours (7 days). The cantilever beam notched impact strength of the aged specimen is tested again, and its retention rate relative to the strength before aging is calculated. Processing performance: On a fixed injection molding machine, a toy part mold with a complex structure was used for trial production, and the severity of flash and burrs on the product was observed.
[0058] The test results show that the embodiments of the present invention successfully achieved a perfect balance of lightweight, high flowability, high toughness, excellent aging resistance, and excellent processing performance. Comparative Example 1 used calcium carbonate, which has a high density and increases melt resistance, resulting in the lowest MFR, making processing difficult, causing severe flash, and exhibiting the worst aging resistance. In Comparative Example 2, replacing the silane coupling agent from KH-570 containing unsaturated double bonds to the amino-based KH-550 led to a significant decrease in interfacial bonding, affecting mechanical properties and aging resistance. Comparative Example 3, without the addition of epoxidized soybean oil, further demonstrated the synergy between KH-570 (providing C=C) and epoxidized soybean oil (providing epoxy groups and interfacial compatibility). Comparative Example 4 lacked processing aids, resulting in poor microsphere dispersion and melt uniformity, and a decrease in both MFR and appearance.
[0059] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.
Claims
1. A lightweight, weatherable PVC material, characterized in that, By weight parts, comprising: 100 parts of PVC resin; 5-25 parts of modified hollow glass microbeads; 20-40 parts of plasticizer; 2-6 parts of composite stabilizer; 0.5-2 parts of lubricant; 0.5-3 parts of processing aid; The surface of the modified hollow glass microbeads is grafted with a silane coupling agent containing unsaturated double bonds. The composite stabilizer comprises a calcium-zinc composite stabilizer and epoxy soybean oil.
2. A lightweight weatherable PVC material according to claim 1, characterized in that, The silane coupling agent containing unsaturated double bonds is γ-(methacryloyloxy) propyl trimethoxysilane.
3. The lightweight weatherable PVC material according to claim 1, characterized in that, The modified hollow glass microbeads have a density of 0.20-0.60 g / cm 3 , and an average particle size of 10-100 μm.
4. The lightweight, weatherable PVC material of claim 1, wherein, The weight ratio of the calcium-zinc composite stabilizer to the epoxy soybean oil is 1:0.5 to 1:
2.
5. The lightweight, weatherable PVC material of claim 1, wherein, The plasticizer is acetyl tributyl citrate.
6. The lightweight, weatherable PVC material of claim 1, wherein, The lubricant comprises an internal lubricant calcium stearate and an external lubricant oxidized polyethylene wax.
7. The lightweight, weatherable PVC material of claim 1, wherein, The processing aid is an acrylate polymer.
8. A process for the production of the light-weight, weather-resistant PVC material according to any one of claims 1 to 7, characterized in that, Comprising the following steps: S1. Pre-mixing the modified hollow glass microbeads with 1 / 3 to 1 / 2 of the total amount of epoxy soybean oil to obtain a pre-mix; S2. Mixing the PVC resin, calcium-zinc composite stabilizer and internal lubricant and heating to 55-65℃; adding the plasticizer and the remaining epoxy soybean oil, continuing to mix and heat to 85-95℃; adding the pre-mix obtained in step S1 and the processing aid, mixing and heating to 105-115℃; finally adding the external lubricant, mixing uniformly to obtain a hot mix; S3. Melting and extruding the hot mix through a double screw extruder, granulating, and obtaining the product.
9. The method of producing a lightweight weatherable PVC material according to claim 8, characterized in that, The pre-mixing in step S1 is carried out at 40-50℃.
10. Use of the light-weight, weather-resistant PVC material according to any one of claims 1 to 7 for the production of a children's toy or a component of a children's toy.